EQUIPOS DE TRABAJO: UNA HERRAMIENTA EFECTIVA PARA LA ADMINISTRACIÃ“N DE LAS EMPRESAS DEL SECTOR MANUFACTURERO EN CIUDAD JUÃREZ - Reyes, Carmina; Cervantes, Teresa; Gamboa, Javier; Quijano, Jorge; Cuevas, Tomás (European Scientific Journal, ESJ, 2012)
The present document aims to determine the role of work teams as an effective tool for large companies in the manufacturing industry in Mexico, specifically in Ciudad Juarez, Chihuahua, as aid for the training of such enterprises, with the aim of improving the efficiency and effectiveness of these. You must take into account that this manuscript will not encompass the scope of SMEs and family businesses. It seeks to develop a guide based on information from companies that are applying this tool to work, its direction and management teams formation, as well as the training necessary for the good management of the teams. In addition it desires to identify some faults that can occur during this process.